Chloroform-based Atherton–Todd-type reactions of alcohols and thiols with secondary phosphine oxides generating phosphinothioates and phosphinates1. Issue 88 (25th September 2015) - Li, Shan; Chen, Tieqiao; Saga, Yuta; Han, Li-Biao
<x xml:space="preserve">Abstract</x> Various valuable phosphinothioates and phosphinates including those with functional groups are readily prepared under mild reaction conditions via chloroform-based Atherton–Todd-type reactions of secondary phosphine oxides with alcohols and thiols, respectively.